Post-traumatic stress disorder amongst surgical trainees: An unrecognised risk?. Issue 3 (June 2017) - Thompson, Christopher V.; Naumann, David N.; Fellows, Jodie L.; Bowley, Douglas M.; Suggett, Nigel
Abstract: Background: Experiences of actual/threatened death or serious injury to patients are commonplace in surgery. Pathological symptoms following stress may lead to Acute Stress Reaction (ASR) and Post-Traumatic Stress Disorder (PTSD). PTSD symptoms of insomnia, anger, poor concentration, hyper-vigilance and exaggerated startle have implications for patient safety. The current study investigates the prevalence of occult, untreated psychological morbidity amongst surgical trainees. Methods: A web-based survey of UK surgical trainees based upon the Impact of Events Scale-Revised (IES-R) was distributed using social media platforms and email. A score of ≥33 was indicative of ASR or PTSD (the former lasting <1 month, the latter >1 month). Additional questions concerned chronicity of symptoms, mentorship, team-working and access to support. Results: For 167 returned surveys the mean age was 32.7 (SD 3.6) years; 102/167 (61%) were male. Mean years in training were 6.1 (SD 3.6). Median IES-R score was 14 (IQR 7–23.5). Of 144 respondents who answered about stress symptoms, 23/144 (16%) had IES-R score ≥ 33; 6 of these had symptoms < 1 month (suggesting ASR); 17 had symptoms lasting >1 month (suggesting PTSD). Those with IES-R ≥ 33 group were more likely to have repeated years of training, and have witnessed severe pain, traumatic injury, and acute haemorrhage. Seven with score ≥ 33 had sought support. Conclusion: Occult psychological morbidity amongst surgical trainees may be higher than in the general population. Recognition and management of this risk is important for the mental health of trainees and the safety of patients.